Effect of the Gel Drying Method on Properties of Semicrystalline Aerogels Prepared with Different Network Morphologies - Glenn A. Spiering; Garrett F. Godshall; Robert B. Moore (Gels, 2025)
The purpose of this study was to investigate the effect of different drying methods on the structure and properties of semicrystalline polymer aerogels. Aerogels, consisting of either globular or strut-like morphologies, were prepared from poly(ether ether ketone) (PEEK) or poly(phenylene sulfide) (PPS) and dried using vacuum drying, freeze-drying, or supercritical CO2 extraction. Vacuum drying was found to result in aerogels with a higher shrinkage, smaller mesopores (with pore widths of 2–50 nm), and smaller surface areas compared to the use of supercritical extraction as the drying method. Freeze-dried aerogels tended to have properties between those of vacuum-dried aerogels and aerogels prepared with supercritical extraction. High network connectivity was found to lead to improved gel modulus, which increased the ability of aerogels to resist network deformation due to stresses induced during drying. The PEEK and PPS aerogel networks consisting of highly connected strut-like features were considerably stiffer than those composed of globular features, and thus shrank less under the forces induced by vacuum drying or freeze-drying. The aerogels prepared from PPS were found to have larger mesopores and smaller surface areas than the aerogels prepared from PEEK. The larger mesopores of the PPS aerogels induced lower capillary stresses on the aerogel network, and thus shrank less. This work demonstrates that preparing PEEK and PPS gels with strut-like features can allow aerogel processing with simpler evaporative drying methods rather than the more complex supercritical drying method.